Impact of Preoperative Opioid Use on Total Knee Arthroplasty Outcomes. (17th May 2017) - Smith, Savannah R.; Bido, Jennifer; Collins, Jamie E.; Yang, Heidi; Katz, Jeffrey N.; Losina, Elena
Abstract : Background: There is growing concern about the use of opioids prior to total knee arthroplasty (TKA), and research has suggested that preoperative opioid use may lead to worse pain outcomes following surgery. We evaluated the pain relief achieved by TKA in patients who had and those who had not used opioids use before the procedure. Methods: We augmented data from a prospective cohort study of TKA outcomes with opioid-use data abstracted from medical records. We collected patient-reported outcomes and demographic data before and 6 months after TKA. We used the Pain Catastrophizing Scale and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) to quantify the pain experiences of patients treated with TKA who had had a baseline score of ≥20 on the WOMAC pain scale (a 0 to 100-point scale, with 100 being the worst score), who provided follow-up data, and who had not had another surgical procedure within the 2 years prior to TKA. We built a propensity score for preoperative opioid use based on the Pain Catastrophizing Scale score, comorbidities, and baseline pain. We used a general linear model, adjusting for the propensity score and baseline pain, to compare the change in the WOMAC pain score 6 months after TKA between persons who had and those who had not used opioids before TKA. Results: The cohort included 156 patients with a mean age of 65.7 years (standard deviation [SD] = 8.2 years) and a mean body mass index (BMI) of 31.1 kg/m 2 (SD = 6.1 kg/m 2 ); 62.2% were female. Preoperatively, 36 patients (23%) had had at least 1 opioid prescription. The mean baseline WOMAC pain score was 43.0 points (SD = 12.8) for the group that had not used opioids before TKA and 46.9 points (SD = 15.7) for those who had used opioids (p = 0.12). The mean preoperative Pain Catastrophizing Scale score was greater among opioid users (15.5 compared with 10.7 points among non-users, p = 0.006). Adjusted analyses showed that the opioid group had a mean 6-month reduction in the WOMAC pain score of 27.0 points (95% confidence interval [CI] = 22.7 to 31.3) compared with 33.6 points (95% CI = 31.4 to 35.9) in the non-opioid group (p = 0.008). Conclusions: Patients who used opioids prior to TKA obtained less pain relief from the operation. Clinicians should consider limiting pre-TKA opioid prescriptions to optimize the benefits of TKA. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.